Increasing Male Students' Interest in Learning Dance with the Peer Tutor Method: An Action Research - Redja Hikmat Gumelar; Agus Budiman; Tatang Taryana (Gondang: Jurnal Seni dan Budaya, 2023)
Dance learning in schools is synonymous with learning movements that have a gentle character. This condition is one of the things that causes men's interest in learning dance to be very weak. Moreover, the tendency of students' interest in learning dance today has been influenced by modern culture such as the existence of modern dance that has developed in society, especially among the younger generation today. When teachers provide traditional dance material, the majority of students consider it too old-fashioned to learn at school. The purpose of this study was to increase male students' interest in learning dance in extracurricular activities by using the peer tutor method. This research uses the Classroom Action Research method with a quantitative approach to find a solution to the problem of weak male students' interest in learning dance in extracurricular dance activities. Data collection techniques were carried out by observation, interviews and questionnaire instruments through google form. Data analysis was carried out by conducting a Paired Sample T Test to see differences in pretest and posttest results. The findings of this study indicate that the peer tutor learning method is able to increase male students' interest through the Lenyepan dance material provided by the teacher in extracurricular dance activities. From the four stages of learning carried out, the results look very significant, the improvement that continues to occur in each phase makes the results of this study show a positive increase. So it can be concluded that the peer tutor learning method is very suitable for attracting male students' interest in dance learning. Judging from the increase in male students' interest in learning dance.